Ga-doped ZnO nanorods: the photocatalytic performance of methylene blue under solar irradiation - Al Ghafry, Sulaiman S. A.; Al-Abri, Mohammed Z.; Al Farsi, Basim; Al Marzouqi, Faisal; Al Farsi, Lamia M.; Roslan, Nur Adilah; Supangat, Azzuliani (Elsevier BV, 2022)
Access to clean water is one of the fundamental needs in our rapid lifestyle; a large amount of water pollution recently threatens this right. These contaminants have highlighted as a challenge to the conventional wastewater treatment process. In this article, a rapid microwave-assisted method has used to synthesize pristine and gallium-doped ZnO nanorods on the glass substrate. Different levels of doping (0.5%, 1%, 3% and 5% Ga) have been investigated. Results show that the morphological properties of nanorods change significantly with Ga doping from 0.5% to 5%. Comparably, the crystalline size and surface roughness are also Ga content dependent. The existence of Ga in the ZnO lattice confirms the effective Ga-doping of ZnO NRs. The 1% Ga doping sample shows significant enhancement in visible light absorption, the recombination of photo generated charge carriers, and rapid degradation at more than 80% within 60 min compared to the pristine sample.